Jessica the jazz fairy - Meadows, Daisy (New York : Scholastic, 2007)
The goblins are making it difficult for Rachel and Kirsty to find Jessica's special ribbon.
RL2.
006-009.
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Fiction; Tate, Kirsty (Fictitious character) -- Fiction; Fairies -- Fiction; Fantasy fiction